Assessment of oral hygiene status among children admitted in intensive care unit at tertiary care Hospital Karachi - Zulifqar Ali; Badil; Nazia Khan (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Oral assessment is the vital responsibility of the nurse that can lead to preventing the illness and maintaining health in the pediatric intensive care unit. The objective of this study was to assess oral hygiene and determine associated factors among children admitted in pediatric intensive care unit at tertiary care public sector hospitals Karachi METHODOLOGY: This Analytical cross-sectional study was accomplished at a tertiary care hospital in the pediatric intensive care unit in Dr. Ruth K.M. Pfau Civil Hospital at Karachi. A consecutive sampling technique was used to approach the study participant. Study participants were approached through a consecutive sampling technique. The calculated sample size was 92, it was calculated by the software "sample size determination in Health Sciences". Beck oral assessment scale (BOAS) was used for data collection. p<0.05 was considered statistically significant. RESULTS: Out of the total 110 study participants, 80(72.75 %) were males, and 30(27.3%) were females, with overall mean age 8.45±2.97 years. In this study, 32(29.1%) children have mild dysfunction, whereas majority of the children have moderate dysfunction 67(60.9%). However severe dysfunction, which is most dangerous, was also found in 11(10.0%) children. According to results, the mild dysfunction and moderate/ severe were found statistically significant with age and gender p<0.038 and 0.013, respectively. CONCLUSION: It is concluded that almost all the children in the Pediatric Intensive Care Unit of a public sector tertiary care hospital were suffering with dysfunctions, and the majority were suffering with moderate to severe dysfunction on the basis of Beck oral assessment scale.